Engineering anatomically shaped vascularized bone grafts with hASCs and 3D‐printed PCL scaffolds. Issue 12 (19th February 2014) - Temple, Joshua P.; Hutton, Daphne L.; Hung, Ben P.; Huri, Pinar Yilgor; Cook, Colin A.; Kondragunta, Renu; Jia, Xiaofeng; Grayson, Warren L.
Abstract The treatment of large craniomaxillofacial bone defects is clinically challenging due to the limited availability of transplantable autologous bone grafts and the complex geometry of the bones. The ability to regenerate new bone tissues that faithfully replicate the anatomy would revolutionize treatment options. Advances in the field of bone tissue engineering over the past few decades offer promising new treatment alternatives using biocompatible scaffold materials and autologous cells. This approach combined with recent advances in three‐dimensional (3D) printing technologies may soon allow the generation of large, bioartificial bone grafts with custom, patient‐specific architecture. In this study, we use a custom‐built 3D printer to develop anatomically shaped polycaprolactone (PCL) scaffolds with varying internal porosities. These scaffolds are assessed for their ability to support induction of human adipose‐derived stem cells (hASCs) to form vasculature and bone, two essential components of functional bone tissue. The development of functional tissues is assessed in vitro and in vivo. Finally, we demonstrate the ability to print large mandibular and maxillary bone scaffolds that replicate fine details extracted from patient's computed tomography scans. The findings of this study illustrate the capabilities and potential of 3D printed scaffolds to be used for engineering autologous, anatomically shaped, vascularized bone grafts. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 4317–4325, 2014.